Impact of airborne particulate matter on skin: a systematic review from epidemiology to in vitro studies - Dijkhoff, Irini M. (Part Fibre Toxicol, 2020)
BACKGROUND: Air pollution is killing close to 5 million people a year, and harming billions more. Air pollution levels remain extremely high in many parts of the world, and air pollution-associated premature deaths have been reported for urbanized areas, particularly linked to the presence of airborne nano-sized and ultrafine particles. MAIN TEXT: To date, most of the research studies did focus on the adverse effects of air pollution on the human cardiovascular and respiratory systems. Although the skin is in direct contact with air pollutants, their damaging effects on the skin are still under investigation. Epidemiological data suggested a correlation between exposure to air pollutants and aggravation of symptoms of chronic immunological skin diseases. In this study, a systematic literature review was conducted to understand the current knowledge on the effects of airborne particulate matter on human skin. It aims at providing a deeper understanding of the interactions between air pollutants and skin to further assess their potential risks for human health. CONCLUSION: Particulate matter was shown to induce a skin barrier dysfunction and provoke the formation of reactive oxygen species through direct and indirect mechanisms, leading to oxidative stress and induced activation of the inflammatory cascade in human skin. Moreover, a positive correlation was reported between extrinsic aging and atopic eczema relative risk with increasing particulate matter exposure.